Peningkatan Kinerja Layanan Organisasi Publik Melalui Penerapan Manajemen Stratejik - Setijabudi, Setijabudi (Jurnal Riset Ekonomi dan Bisnis, 2010)
Implementation of stratejic management in public organizations will be different from a private company in general due to differences in the characteristics of both organizations. Public sector organizations do not emphasize the goals of the organization in search for income but rather on a quality service. Public services must receive serious attention by local governments, since public services directly or indirectly will affect the quality of public welfare. Local governments with high-performing public service that will allow increased public access to various services provided by local governments. Organization's success in implementing its strategy cannot be separated from the role of subordinates and employees. Understanding and uniting willpower of members of public organization to promote the organization and to improve public service is the basis of a successful capital management strategy of the public organization.Keywords: Stratejic, management, improvement, public, service, performance, non-public, organization